The Integration of Character Education in Arabic Learning at Muhammadiyah Elementary School 4 Samarinda - Hidayat, Ahmad Fadhel Syakir; Huda, Miftahul; Amalia, Dian Risky; Suja, Aidillah; Sulaikho, Siti (Borneo International Journal of Islamic Studies, 2022)
The majority of people in Indonesia have periodically attended elementary school, junior high school, high school, and university-level formal education programs. It should go without saying that those who have previously gotten education do not generally have good moral character. There are currently a growing number of offenses that transgress religious principles. As a result, character education for both students and teachers is required, and this can be done by including character traits into the formal curriculum. The implementation of learning processes, execution procedures, and assessment processes can accomplish this. The 2013 curriculum includes character education. The emphasis on learning includes affective and psychological learning in addition to cognitive learning. Due of this, character education is required. As a result, character education must be incorporated into every topic taught in formal schools, including the study of Arabic. The goal of this study is to ascertain the planning for integrating character education into the study of Arabic, the actual integrating of character education into the study of Arabic, the evaluation of that integration, as well as the effects of that integrating character education on the students at Muhammadiyah 4 Samarinda Elementary School. A descriptive qualitative approach is used in this study. Observation, interviewing, and documentation are the methods used to acquire data. Miles and Huberman theory is employed in the data analysis. According to the study's findings, the planning process should have 13 character values, the implementation and evaluation processes should have 13 character values, and the implications should have 11 character values.